Analysis of thermal deformation and influencing factors in shrink-fitting assembly of aluminum alloy drill pipe. (October 2016) - Wang, Xiaofeng; Liu, Baochang; Gao, Ke; Meng, Qingnan; Sun, Youhong
In shrink-fitting assembly process of aluminum alloy drill pipe with steel joint, the relationship between cooling water velocity, initial heating temperature, and thermal deformation of the steel joint is an important factor to ensure the long-term reliability of the connection and the performance. In this article, the shrink-fitting assembly experiment of aluminum pipe with steel joint was conducted and the accurate experimental data were obtained for temperature field. A finite element method was then applied to simulate the temperature field of steel joint and compared with the experimental results. Based on the thermo-elasticity theories, an analytical solution was developed to calculate the thermal deformation in radial direction within the same cross section. A least-square fitting procedure was used to determine the thermal deformation of steel joint. A relationship diagram among these three factors was established, which is particularly important in predicting the minimum heating temperature of steel joint and the minimum cooling water velocity. Based on the above analysis, a method to select the initial heating temperature and the cooling water velocity was provided and the optimum values of the magnitude of interference, the initial heating temperature, and the cooling water velocity were obtained.